The Influence of Financial Literacy, Financial Technology and Fear of Missing Out on the Financial Behavior of Generation Z - Hemayanti, Niril; Nurabiah, Nurabiah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Generation z is a group that is very familiar with digital technology and social media, because generation z grows and develops in the digital era which affects almost all aspects of life including financial behavior. The purpose of this study is to examine how the influence of financial literacy, financial technology and FOMO on the financial behavior of generation z. The population of this study is 29,792 people. The number of sample data in this study is 620 people. The sampling method used proportionate stratified random sampling. The data processing in this study applies the Partial Least Square (PLS) technique with the SmartPLS 4.0 software application. The results of the analysis of this study said that financial literacy and financial technology have a significant positive effect on financial behavior. Fear of missing out has a significant negative effect on financial behavior.